Determinación de la concentración de plomo de socavones en la minería artesanal del Cerro El Toro, Shiracmaca - Huamachuco, La Libertad - 2011 - Figueroa Sánchez, José Irvin (2011)
The purpose of this research is to determine the concentration of lead in soils impacted by artisanal mining in six areas surrounding the Cerro El Toro-Shiracmaca-Huamachucousing atomic absorption spectroscopy ,and also provide information on the consequences of that the presence of lead in high concentrations and emphasize preventive measures. Data collection accomplished in three phases: diagnosis, sample collection phase and phase determination of lead and then by atomic absorption spectrophotometry is calculated the concentration of lead in the sample in a limited range of concentrations. The results were: In tunnel N°1: 21.1 mg / kg, tunnel N°2: 22.35 mg / kg, tunnel N° 3: 218.20 mg / kg, tunnel N°4: 9.32 mg / kg, tunnelN°5: 28.50 mg / kg and tunnel N°6: 148.60 mg / kg. This also informed the public of preventive measures and the effects on health and environment, using didactic material